Silício no manejo pré e pós-colheita da podridão parda (monilinia fructicola) no pessegueiro - Pavanello, Elizandra Pivotto (2016)
Brown rot is the main diseases of peaches, with pre and postharvest losses. Control it is difficult because the fungus infect fruit and remain latent until conditions are favorable to its manifestation. Therefore, to understand the role of latent infection of the disease incidence and find strategies to minimize losses, with low environmental impact, is essential for sustainable crop management. This thesis consists of four papers that resulted from work with the following objectives: to study the relationship between latent infection and the occurrence of postharvest brown rot; to evaluate the effect of preharvest fungicide application on the Monilinia fructicola control during storage and marketing of peaches; to investigate the pre and postharvest applications of silicon on the brown rot control in peach. They were used peaches of Eldorado and Pepita cultivars, in field experiments involving preharvest spraying of fungicides and pre and postharvest applications of silicon and experiments in refrigerated storage conditions at -0.5 ° C. Iprodione, tebuconazole and difenoconazole are effective in brown rot control in the field conditions, while in postharvest, the incidence was controlled in 96.2% with iminoctadine. These products decreased the incidence of injuries resulting from latent infections. There is a high correlation between the presences of latent infections in preharvest with the incidence of the disease in postharvest, with most of the damage after cold storage resulting from the latent infections of Monilinia fructicola. Foliar application of 6 g L-1 sodium silicate or sodium metasilicate is effective in controlling the disease without causing phytotoxicity to the plants. Six sodium silicate applications had the same effect as six fungicides applications to brown rot control in peaches Eldorado . Postharvest sodium metasilicate application, in 6 g L-1, reduced the diseases incidence but caused fruit skin darkening. Physical defense mechanisms of the plants are affected by silicon application, because it increased the element content in the leaves and fruits, and increased skin texture. However, the effect of silicon on the biochemical defense mechanisms may involve the synthesis of polyphenols, because in the one year of search we found a higher content of these compounds in fruit treated with silicon. In general, products based on silicon, applied alone or intercalated with fungicides, control the disease in pre and postharvest, allowing a decrease in fungicide use and production cost.